Data Mining Technique for Improving Student Performance - Patel, BR (International Journal of Computer Sciences and Engineering, 2025)
Data mining technology is a procedure for analyzing large amounts of available data and extracting useful information and knowledge to support critical decision-making processes. Data mining can be applied to various applications in the field of education to improve student performance. Educational data mining is developing rapidly and is an important technology for data analysis in the field of education. This paper shown different classification algorithms of data mining those are used for development of a data mining model for predictions of performances of students, on the basis of their personal demographic and academic information. This paper analyze and evaluate the students‟ performance by applying data mining classification algorithms in weka tool.